2001
DOI: 10.4049/jimmunol.167.3.1338
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Expression of CD95 Ligand on Thyroid Follicular Cells Confers Immune Privilege upon Thyroid Allografts

Abstract: Constitutive Fas ligand (FasL) expression by specialized cells in the body participates in the immune privilege status of tissues containing these cells. This property has been used to prevent rejection of allogeneic grafts. Nevertheless, the mechanism responsible for such protection has not been fully elucidated. Unfortunately, grafting of FasL transgenic (TG) tissues has been unsuccessful. We have generated TG mice expressing FasL (soluble + membrane bound) on thyroid follicular cells (TFC), and used them to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 42 publications
3
30
1
Order By: Relevance
“…68,69 This notion is consistent with the observation that CD4 ϩ T cells are important to FasLmediated immunoregulation since the depletion of these cells abolishes the protection conferred by FasL. 56 Particularly, naturally occurring CD4 ϩ CD25 ϩ Tregs were recently found to be resistant to apoptosis, possibly owing to their expression of high levels of antiapoptotic genes. 70 In transplantation settings, immunomodulation may not only prevent rejection, but also lead to central tolerance due to thymic selection of newly emerging T cells 71,72 continuously exposed to circulating donor antigens.…”
Section: Localized Immunomodulation With Faslsupporting
confidence: 74%
See 2 more Smart Citations
“…68,69 This notion is consistent with the observation that CD4 ϩ T cells are important to FasLmediated immunoregulation since the depletion of these cells abolishes the protection conferred by FasL. 56 Particularly, naturally occurring CD4 ϩ CD25 ϩ Tregs were recently found to be resistant to apoptosis, possibly owing to their expression of high levels of antiapoptotic genes. 70 In transplantation settings, immunomodulation may not only prevent rejection, but also lead to central tolerance due to thymic selection of newly emerging T cells 71,72 continuously exposed to circulating donor antigens.…”
Section: Localized Immunomodulation With Faslsupporting
confidence: 74%
“…54 These initial observations were followed by a series of studies using FasL as an immunomodulatory agent with variable results. While some studies reported extended survival of allogeneic grafts, such as liver, kidney, thyroid, pancreatic islets, lung, and cornea, 55,56 others noted accelerated rejection of syngeneic and allogeneic grafts. [57][58][59] A common denominator in the latter studies was the presence of massive inflammatory infiltrates, particularly neutrophils, in FasL-expressing tissues and organs, suggesting that rejection was initiated by a delayed-type hypersensitivity reaction.…”
Section: Localized Immunomodulation With Faslmentioning
confidence: 99%
See 1 more Smart Citation
“…the eye and testes) by binding Fas on infiltrating leukocytes (15)(16)(17)(18)(19). However attempts to exploit this latter function for allograft protection have been complicated by different roles for soluble and membrane-bound FasL and the ability of cells to resist injury (20). Transgenic expression of FasL on islet cells induces greater cytotoxicity of neutrophils (21) while transgenic FasL expression in endogenous Fas-bearing cells may lead to a form of self injury (22,23).…”
Section: And Cd8mentioning
confidence: 99%
“…However, rodent transplantation experiments involving FasL have yielded conflicting results. Several groups demonstrated enhanced allograft survival following direct transfection of FasL cDNA into allografts (Li et al, 1998;Tourneur et al, 2001). Cotransplantation of FasL-negative allografts with FasL-expressing cells was also reported to prevent allograft rejection (Korbutt et al, 1997;Takeda et al, 1998).…”
mentioning
confidence: 99%